Rénovation de deux structures scolaires, au Danemark : Quelles évolutions, quelles perspectives pédagogiques ? - France Roy
This article discusses the case of two schools, that are "famous", each in her own way in Denmark, which recently received ambitious expansion and renovation programs : Rødding Højskole (Rødding Folkhighschool) and Munkegaardsskolen (Munkegaard's school). These projects are part of the history of these schools, of the country, and are based on a child's or man's conception specifically developed in the Nordic countries. They show a need to adapt buildings to technical developments and constraints, and a wish to improve education and teaching methods. Our article reports, for part, of the architectural evolution of these two schools, each understood in historical, social and educational context ; then we make a comparison of the two projects and of their foundations, and we open research perspectives on the pedagogical contribution that these architectural evolutions could induce.